Employee Engagement as a Mechanism Linking Self-Confidence, Work-Life Balance, and Performance - Azhar, Muhammad Farich; Widhiastuti, Hardani; Dewi, Rusmalia (Journal Corner of Education, Linguistics, and Literature, 2026)
This study examines how self-efficacy and work-life balance contribute to employee performance through employee engagement as an intermediary mechanism. This study was prompted by differences in performance between divisions, varying levels of employee self-confidence, and challenges in maintaining work-life balance due to fluctuating workloads. A quantitative approach was used with path analysis based on Partial Least Squares (PLS). The sample consisted of employees with a minimum of five years of service, who were selected to represent stable performance conditions. The findings show that self-confidence significantly increases employee engagement and performance. Work-life balance also plays a significant role in strengthening engagement and improving performance outcomes. Furthermore, employee engagement mediates the effects of self-confidence and work-life balance on employee performance. These results highlight the importance of human resource strategies that foster employee self-confidence, support work-life balance, and encourage active participation to achieve sustainable performance improvement.